Plasma production and composition from hypervelocity impacts on solar cell cover glass. (November 2022) - Fereydooni, Kimia; Evans, Alexandra Ilinskaya; Lee, Nicolas; Close, Sigrid
Highlights: New technique for calculating the total hypervelocity impact charge is presented. New technique for calculating the power law for different species is presented. Charge production power law is species specific and depends on spacecraft charge. Species formation mechanism is associated with dissociation/ionization of molecules. Abstract: Satellites are subjected to detrimental effects from the space environment, including impacts by orbital debris and meteoroids that can cause mechanical or electrical damage. While mechanical damage is well studied, electrical effects resulting from hypervelocity impact (HVI) remain poorly understood. In HVIs, where the projectile speed exceeds the speed of sound in the target material, the impact energy ionizes the material near the surface, creating a plasma that can cause radio frequency emission. This emission is the main source of electrical anomalies in satellites, but the mechanism behind its creation is still unknown. Ground-based experiments have been used to characterize HVI plasma, including the empirical power law relations that describe the impact charge produced as a function of impactor mass and speed. Quantifying these power law relations gives us a better understanding of the species formed in the impact which can eventually lead to plasma evolution models and help us first, understand the mechanism behind radio frequency emission and second, ways to prevent its damage to the satellites. In this paper, we interpret the results of the HVI experiments on solar cell coverglass targets and identify the potential chemical or molecular reactions that form the impact ion species. This is done by looking simultaneously at multiple data sets for different species within the same impact configuration, and using a new technique for quantifying the power law relations for each emitted species. We use time of flight analysis (TOF) to detect the charged particle compositions and determine their initial speeds. The results suggest that the charge production power law is species specific, with different formation mechanisms involved in a single HVI event, some of which are associated with dissociation and some with ionization of a molecule. Our results also show that electrons have different power laws that depend on the spacecraft surface charge. TOF measurements of ions from impact events on solar cell cover glass shows the presence of Si O + and SiO 2 − as the dominant species present in plasmas on positively and negatively charged targets, respectively, as well as the formation of Fe O + .